2023
DOI: 10.3847/2041-8213/acccfb
|View full text |Cite
|
Sign up to set email alerts
|

A New Definition of Exoplanet Habitability: Introducing the Photosynthetic Habitable Zone

Abstract: It may be possible to detect biosignatures of photosynthesis in an exoplanet’s atmosphere. However, such a detection would likely require a dedicated study, occupying a large amount of telescope time. It is therefore prudent, while searching for signs of life that we may recognize, to pick the best target possible. In this work, we present a new region, the photosynthetic habitable zone (PHZ)—the distance from a star where both liquid water and oxygenic photosynthesis can occur. It is therefore the region wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…They concluded that pigments would need roughly twice the number of 𝜋-electrons for 𝑇 𝑠 < 3000 K compared to 𝑇 𝑠 ∼ 6000 K, arriving to the same conclusion as Duffy et al. Finally, the feasibility of oxygenic photosynthesis, such as microscopic algae (Hall et al, 2023) and vascular plants (Wolstencroft and Raven, 2002), have been considered within a habitable zone. These predicted oxygenic photosynthesis to perform best around hotter F-type stars (6000 < 𝑇 𝑠 < 7500 K).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…They concluded that pigments would need roughly twice the number of 𝜋-electrons for 𝑇 𝑠 < 3000 K compared to 𝑇 𝑠 ∼ 6000 K, arriving to the same conclusion as Duffy et al. Finally, the feasibility of oxygenic photosynthesis, such as microscopic algae (Hall et al, 2023) and vascular plants (Wolstencroft and Raven, 2002), have been considered within a habitable zone. These predicted oxygenic photosynthesis to perform best around hotter F-type stars (6000 < 𝑇 𝑠 < 7500 K).…”
Section: Introductionmentioning
confidence: 84%
“…It should also be noted that ŕaring may actually support volcanism which can replenish atmospheres (Grayver et al, 2022). Overall, a more intricate habitable zone of photosynthesis should be explored in subsequent work (Hall et al, 2023).…”
Section: Discussionmentioning
confidence: 99%